EFEKTIVITAS PEMBERIAN REBUSAN KUNYIT ASAM TERHADAP PENURUNAN NYERI HAID PRIMER PADA REMAJA PUTRI - Melia Aprina; Rummy Islami Zalni; Qori Armiza Septia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Dysmenorrhea is pain or pain in the lower abdomen that occurs when women experience the menstrual cycle, this problem causes 14% of adolescent patients to often not attend school and do not carry out daily activities. Dysmenorrhea can be treated by using a sour turmeric drink. The purpose of this study was to analyze the effectiveness of giving sour turmeric decoction to reduce primary menstrual pain in adolescent girls. The research method used in this study is a quasi-experimental method. The sampling technique used purposive sampling with a total of 18 respondents. The instrument used is a Numeric Rating Scale questionnaire. Analysis of the data used is the Wilcoxon Signed Rank Test and the Mann Whitney U-Test. The average pain scale before being given turmeric acid drink was moderate pain. while the average pain after being given turmeric acid drink was 68.8% mild pain and 31.2% no pain. Statistical test analysis using the Wilcoxon Signed Rank Test obtained a p-value of 0.000 0.05, indicating that there is an influence between sour turmeric drink in 8th grade students and primary dysmenorrhea at SMP Negeri 47 Pekanbaru. The conclusion of this study is that there is a significant difference in changes in the pain scale of 8th grade students with primary dysmenorrhea. Based on this research, it is suggested that students drink 100cc of sour turmeric per day during menstruation as an alternative to reduce pain scale.Keywords: Turmeric Tamarind Drink, Dysmenorrhea